Current therapeutic approaches to diabetic neuropathy - ELÇİOĞLU, HATİCE KÜBRA (MARMARA UNIV, FAC MEDICINE, 2016)
Development of diabetic peripheral neuropathy plays many metabolic pathways. These pathways vary redox capacity of the cell, ROS (reactive oxygen species) production increases. Increased oxidative stress disrupts neural functions,, causing apoptosis of neurons and Schwann and glial cells in the peripheral nervous system. Many therapeutic agents that act on these pathways are tested in DPN (diabetic peripheral neuropathy) treatment. Although the mechanisms which causes DPN are fully understood, researches continue due to lack of effective treatment of this disease. In order to prevent progression of the disease, the patient's blood glucose levels are controlled. In the treatment of DPN; TCA's, SSRI's and alpha 2-delta calcium channel ligands are used. If a single drug is not enough drug combinations are usable. TCA combination with each other or opioid-gabapentin combination are preferred type of treatment. Anticonvulsant drugs don't play a role symptoms underlying pathology of DPN directly. They only remove diabetic neuropathic pain with indirect mechanism. The use of these drugs to reduce symptoms improves the quality of life in patients responding. Natural resources for the effective treatment of DPN has been discovered. To develop new drugs the mechanisms involved in disease research and clinical trials continue. Perhaps discovered drug molecules research result will lead to real cure rather than symptomatic relief.
Keywords: Diabetic peripheral neuropathy; Hyperglycemia; Mechanism-based treatment; Symptomatic treatment; Novel agents; PERIPHERAL NEUROPATHY; DOUBLE-BLIND; COMPLICATIONS; PLACEBO; RELEASE; TRIAL; PAIN